Antiviral effects of grape seed extract against feline calicivirus, murine norovirus, and hepatitis A virus in model food systems and under gastric conditions. (December 2015) - Joshi, Snehal S.; Su, Xiaowei; D'Souza, Doris H.
Abstract: Grape seed extract (GSE) has antiviral activities against hepatitis A virus (HAV) and human norovirus surrogates (feline calicivirus (FCV-F9) and murine norovirus (MNV-1)). The objectives of this study were to determine (1) time and dose-dependence of GSE against FCV-F9, MNV-1, and HAV at room temperature (RT) and 37 °C over 24 h; and (2) GSE effects in model foods (apple juice (AJ) and 2% milk) and simulated gastric conditions at 37 °C. Viruses at ∼5 log PFU/ml were treated with 0.5–8 mg/ml GSE prepared in water, AJ, milk or gastric juices, or water over 24 h at RT or 37 °C. Infectivity of triplicate treatments was evaluated using plaque assays. GSE effects increased with time and concentration. GSE at 1 mg/ml in AJ reduced MNV-1 to undetectable levels after 1 h and by 1 log in milk after 24 h. GSE at 1 and 2 mg/ml in AJ reduced HAV to undetectable levels after 1 h, while 2 and 4 mg/ml GSE in milk caused ∼1 log reduction after 24 h. GSE at 2 mg/ml in intestinal fluid reduced FCV-F9, MNV-1 and HAV to undetectable levels after 6 h. GSE appears to be a suitable natural option for foodborne viral reduction. Highlights: Antiviral activity of grape seed extract (GSE) increased with time and dose. GSE effects decreased in complex food matrices such as milk. GSE shows potential as preventive and therapeutic options against foodborne viral illness.